Interactivity, game creation, design, learning, and innovation : 6th International Conference, ArtsIT 2017, and second International Conference, DLI 2017, Heraklion, Crete, Greece, October 30-31, 2017, Proceedings /: 6th International Conference, ArtsIT 2017, and second International Conference, DLI 2017, Heraklion, Crete, Greece, October 30-31, 2017, Proceedings. (2018) - Unknown
No abstract available